Le temps des nouveaux guerriers : le héros culturel, figure de la reconquête identitaire et territoriale - Crystel Pinçonnat (Amnis)
Through the analysis of Ceremony, Wolfsong and Zia Summer, this article studies how Leslie Marmon Silko, Louis Owens and Rudolfo Anaya — writers who claim their Native American or chicana identities — represent, in what could be qualified as “identity narratives”, the symbolical reappropriation by a cultural hero of the ancestral territory, historically conquered.